Impact of weaning procedures on Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) circulation in the nursery section - Pia R. Heiselberg; Charlotte Sonne Kristensen; Lise Kirstine Kvisgaard; Lars Erik Larsen (BMC Veterinary Research)
Abstract The impact of different weaning strategies on the downstream circulation of PRRSV has not been widely described. It is, however, believed that mixing pigs of different age groups is increasing the risk of PRRSV circulation in the nursery section. In this study, pigs were sampled in three herds that performed “mixed at weaning (MIX)” and three herds that performed “all in/all out at weaning (AIAO)”. MIX included holding underweighted piglets back in containers for two weeks and then move them to nursery facilities with newly weaned piglets from subsequent batches. Oral fluid samples were collected from four batches of pigs in each herd, three times from weaning until 30 kg for each batch, and tested for PRRSV and PRRSV antibodies. Herds that performed MIX at weaning had an eightfold increase in risk of detecting PRRSV in oral fluids compared to herds with AIAO. In total, 41 oral fluid samples from eight batches in MIX herds and five oral fluid samples from two batches in AIAO herds tested positive for PRRSV. The PRRSV ELISA S/P ratio in oral fluid samples from weaners seem to decrease in most of the batches in the AIAO herds and to increase in most MIX herds. In addition to oral fluids, tongue tip samples were collected from dead pigs and tested for PRRSV. In 17 of 23 batches the results of the tongue tip samples correlated with the results of the oral fluid samples (κ = 0.44) indicating a good agreement between the two materials for sampling. Overall, the results of the study confirmed that the weaning strategy had a significant impact on the circulation of PRRSV post weaning.